Georgias GALILEO: A Step into the Future - Russel, Ralph E.; Beard, Charles E.; Gaumond, George R.; Penson, Merryll S.; Potter, William G.; Williams, Jayne (DESIDOC Journal of Library & Information Technology, 2002)
The article describes a telecommunications network conceptualized in the University System of Georgia for educational, economic, technological and cultural development of all sections of users. The various aspects of GALILEO and technological resources used are presented. http://dx.doi.org/10.14429/dbit.16.1.3168